Gestão de conflitos em organizações públicas: uma análise em órgãos municipais - Witzel, Ana Claudia Paes (2020)
Internal conflicts in organizations can interfere directly or indirectly in the organizational environment and in work relations. In this line, it is important to study conflict management by Human Resources Manager, as well as the analysis of the possibility of using consensual methods as management alternatives related to prevention practices, and the management of internal conflicts involving public servants. The general objective of the present research is to identify in the municipal public agencies which are the main internal conflicts and their possible consequences, to then verify if it exists and how it is carried out by the managers. Therefore, the bibliography review deals with conflicts, organizational culture, people management and conflict management, followed by a Systematic Bibliographic Review specifically on conflict management in Public Administration. Next, a field study was carried out in municipal indirect administration in the cities of São Carlos, Araraquara and Rio Claro. In this way, it was possible to observe the predominance of conflicts related to the content and process of the tasks and, although it was verified the lack of specific and institutional mechanisms for conflict management in the government agencies studied, it was possible to observe the existence of professionals trained in conflict management , mainly the managers of the Human Resources Manager. As general conflict management techniques, the agencies studied make use of dialogue and communication mechanisms, in addition to mediation and negotiation practiced by managers, including Human Resources Manager and technical area chefs.